A Conceptual Study on Reasons of Industrial Sickness- With Reference to Joinery Mills of The J (Global Journal of Management and Business Research, 2012)
The researcher did an empirical study to find out the opinion of the employees of Jammu
Keywords: Jammu Kashmir Industries Ltd; Industrial Sickness; Financial Reasons and Technological Changes; revival; managerial inability; obsolete technology